"Scientific and technological density of regions : the impact on firms' competence to innovate" - Jean - Alain Héraud; Francis Munier; Patrick Rondé (European Regional Science Association (ERSA), 2001)
The purpose of the paper is to present possible approaches of the innovative potential of the regions, with an empirical application concerning the relation between characteristics of regions (scientific and technological density) and the firm's competencies. Regions, which are territories with specific institutional and techno-economic characteristics, will be considered here as significant contexts for innovation processes. By using the word “context”, we want to underline the importance of regional characteristics, even in a globalised economy, but we are reluctant to speak of regional “system” without carefully analysing the possible meaning of such a notion. RIS is a useful concept if it one stresses its cognitive content – a way of interacting that leads to specific competence to innovate – but can be misleading if understood as an ex ante given network of actors and infrastructures. An important characterisation of territorial specificity in evolutionary terms is the cognitive potential of actors. For instance, firms' capabilities vary to a large extent following the type of innovation under consideration : outcome of science-based R&D, particular competitiveness in marketing innovative products, incremental improvements through learning by using (N. Rosenberg) or other sort of learning by interacting (B-A. Lundvall). To give an empirical example, we will use the results of a survey of the French industry focusing on the innovative competence of the firms. We have developed an econometric model for testing the influence of the regional scientific and technological context on the nature of the “competence to innovate” declared by the firms in the inquiry. This study is an opportunity to cast light on the concept of critical interfaces evoked by K. Pavitt (1998), by underlining several schemes of industrial development according to specific characteristics of industries and regions. Designing differentiated regional policies on the basis of such an analysis seems to be possible.
Keywords: 330